2009
DOI: 10.4103/0974-2727.59701
|View full text |Cite
|
Sign up to set email alerts
|

Nonfermenting Gram-Negative Bacilli Infections in a Tertiary Care Hospital in Kolar, Karnataka

Abstract: AIM:Nonfermenting gram-negative bacilli (NFGNB), which are saprophytic in nature, have emerged as important healthcare-associated pathogens. They exhibit resistance not only to beta lactam and the other groups of antibiotics, but also to carbapenems. This study was undertaken to identify the nonfermenters isolated from various clinical samples, to assess their clinical significance, to know the type of healthcare-associated infections they caused, and to know their anti-microbial sensitivity pattern.Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
69
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 5 publications
(11 reference statements)
18
69
2
6
Order By: Relevance
“…Similar higher sensitivity to aminoglycosides was reported by Malini et al, (2009) (100%) and Kiran et al, (2013) (93.3%). A sensitivity of 75% to Trimethoprime/ sulphamethaxazole in this study is less as compared a sensitivity of 100% reported by Malini et al, (2009), Kiran et al, (2013 has reported a sensitivity of 86.7% for trimethoprime/ sulphamethaxazole, colistin was 100% sensitive in the present study which is much higher than 56.1% reported by Nicodemo et al, (2004). As for as sensitivity of Sphingomonas paucimobilis 100% to trimethoprime/ sulphamethaxazole, tigecycline, minocycline and meropenem and cefoperazone/ sulbactam is concerned it is difficult to comment on there therapeutic usefulness as studies for Sphingomonas paucimobilis could not be found.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Similar higher sensitivity to aminoglycosides was reported by Malini et al, (2009) (100%) and Kiran et al, (2013) (93.3%). A sensitivity of 75% to Trimethoprime/ sulphamethaxazole in this study is less as compared a sensitivity of 100% reported by Malini et al, (2009), Kiran et al, (2013 has reported a sensitivity of 86.7% for trimethoprime/ sulphamethaxazole, colistin was 100% sensitive in the present study which is much higher than 56.1% reported by Nicodemo et al, (2004). As for as sensitivity of Sphingomonas paucimobilis 100% to trimethoprime/ sulphamethaxazole, tigecycline, minocycline and meropenem and cefoperazone/ sulbactam is concerned it is difficult to comment on there therapeutic usefulness as studies for Sphingomonas paucimobilis could not be found.…”
Section: Resultssupporting
confidence: 74%
“…The various clinical specimens from which NFGNB were isolated are pus (38), urine (21), blood (16), sputum (6), BAL (6), ET secretions (8) and other body fluids (26). The predominant isolate was Pseudomonas species (79), followed by Acinetobacter (27), Burkholderia cepacia complex (7) In recent years isolation of NFGNB has gained importance with increasing reports of these bacteria relating them to hospital outbreaks or health care associated infections (Malini et al, 2009). The most common of these NFGNB are Pseudomonas and Acinetobacter (Ramphal et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Similar trends have also been reported by a study of Eastern India, where 55% patients were males and 45% were females [25]. While study from Rotak has revealed that males and females were equally susceptible to the infection [21].…”
Section: Discussionsupporting
confidence: 71%
“…In a study from Kolar, Karnataka showed saprophytic nature of non-fermenting Gram-negative bacilli as the potent pathogen that exhibits resistant not only to beta-lactam and other antibiotics but also to carbapenems [21]. The sensitivity test was performed by Kirby-Bauer disc diffusion methods.…”
Section: Discussionmentioning
confidence: 99%
“…accounted for about 20%. 14,16,17 Equally, 72.9% of infections with nonfermenter bacilli were reported in Kolar (India).…”
Section: Serratia Liquefaciens Serratia Marcescensmentioning
confidence: 99%